Sosiologi Lingkungan Dalam Lontar Taru Pramana: Manusia, Lingkungan, Dan Pengobatan Tradisional Bali - Adnyana, Putu Eka Sura (JURNAL YOGA DAN KESEHATAN, 2021)
Lontar Taru Pramana is a lontar containing many types of plants that can be used in traditional medicine. Through the contents of Taru Pramana's lontar text, it is possible to trace the types of plants that have lived and are still growing in Bali's natural ecosystem, of course, with an environmental sociology perspective. The relationship between environmental sociology and Taru Pramana's lontar text semiotics explains the meaning of the relationship between humans and the environment. Three conceptions view nature in environmental sociology, namely: 1) Sustainable use of natural resources; 2) "arcadian" approach to the interpretation of nature; 3) natural social construction approach. This conception of nature as a resource has three main characteristics. First, nature is instrumental, which means that nature has value when other values can be manifested through it. Both realms function as a supplier of human material needs, such as food production, health, the availability of space for life, and a supplier of energy and materials. The three definitions of nature are generally closely related to natural science. The preservation of Taru Pramana plants is very important in addition to environmental harmony and as a form of human relations with palemahan (environment). Four types of rationality for human development. First, traditional rationality. The Second, effective rationality. Third, value-oriented rationality. Fourth, instrumental rationality. The ideology of Taru Pramana's text is the preservation and planting of medicinal plants in the ecosystem of traditional Balinese medicine.